INTEGRATED MEASUREMENT SYSTEM FOR ATHLETE HEALTH: HEART RATE, BLOOD OXYGEN, AND BODY TEMPERATURE MONITORING - M.Ilyasa; Ockta, Yovhandra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Athlete health monitoring is critical for optimizing performance and ensuring physical well-being. This study presents an integrated non-invasive system designed to measure key physiological parameters: heart rate, blood oxygen saturation (SPO2), and body temperature. Utilizing infrared LED and photodiode sensors placed on the fingertip, the system detects changes in blood volume, correlating them with heart rate fluctuations. Pulse oximetry, employing red and infrared light wavelengths, accurately measures SPO2 levels by analyzing light absorption through finger tissues. Results from testing show promising accuracy with an average error of 0.89% for SPO2 measurements and 3.095% for heart rate measurements. Body temperature readings exhibit an average error of 0.78%, underscoring the system's reliability in non-invasively monitoring temperature changes. Challenges such as environmental influences and sensor calibration are addressed to ensure consistent and precise measurements. Future enhancements may incorporate advanced signal processing techniques and artificial intelligence to further refine measurement accuracy and reliability. This integrated system holds significant potential for enhancing athlete health management, aiding in early detection of physiological anomalies, and optimizing performance through real-time health monitoring